2010
DOI: 10.1182/blood-2009-09-242875
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells and the neurofibroma microenvironment

Abstract: Neurofibromatosis type 1 (NF1) is the most common genetic disorder with a predisposition to malignancy and affects 1 in 3500 persons worldwide. NF1 is caused by a mutation in the NF1 tumor suppressor gene that encodes the protein neurofibromin. Patients with NF1 have cutaneous, diffuse, and plexiform neurofibromas, tumors comprised primarily of Schwann cells, blood vessels, fibroblasts, and mast cells. Studies from human and murine models that closely recapitulate human plexiform neurofibroma formation indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
97
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 70 publications
(101 reference statements)
1
97
0
2
Order By: Relevance
“…It is currently unclear whether there is a corresponding phenotypic switch from inflammatory M1 macrophages to synthetic M2 macrophages in NF1. Interactions between inflammatory cells and connective tissue cells leading to proliferative and fibrotic consequences are likely, but still only partially understood (Staser et al 2010;Prada et al 2013). Increased release of TGF-β in particular from mast cells and/or macrophages is suspected as being a driving force in the development of both gingival overgrowth and neurofibromas (Saito et al 1996;Tipton and Dabbous 1998;Ling et al 2005;Yang et al 2006).…”
Section: Gingival Overgrowth and Cancermentioning
confidence: 99%
“…It is currently unclear whether there is a corresponding phenotypic switch from inflammatory M1 macrophages to synthetic M2 macrophages in NF1. Interactions between inflammatory cells and connective tissue cells leading to proliferative and fibrotic consequences are likely, but still only partially understood (Staser et al 2010;Prada et al 2013). Increased release of TGF-β in particular from mast cells and/or macrophages is suspected as being a driving force in the development of both gingival overgrowth and neurofibromas (Saito et al 1996;Tipton and Dabbous 1998;Ling et al 2005;Yang et al 2006).…”
Section: Gingival Overgrowth and Cancermentioning
confidence: 99%
“…Mast cells can also be identified by other histochemical techniques: for example, by the use of dyes such as toluidine blue solution (31) , and by immunohistochemistry using tryptase (27) , CD 117 (c-kit) or calretinin (11) as markers. Few studies have identified mast cells in neurofibromas by immunohistochemical and histochemical methods, despite the important role attributed to these cells in the pathogenesis of this lesion (14,33,35) . The identification of mast cells, even in small numbers, can aid in the diagnosis of this neoplasm, particularly if the identification is associated with other immunomarkers of neurofibromas.…”
Section: Discussionmentioning
confidence: 99%
“…The consequent mast cell migration causes the secretion of the growth factors and cytokines necessary for the initiation and progression of the tumor, as well as the factors necessary for neoangiogenesis, including nerve growth factor (NGF), vascular endothelial growth factor (VEGF), fibroblast growth factor, transforming growth factor beta (TGF-β), and others. Fibroblasts, Schwann cells, perineural-like cells and endothelial cells with a mutation in one of the NF1 alleles (Nf1 +/-) seem to be responsive to the neoplastic environment (14,33,35) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This tumor essentially is composed of Schwann cells arising from a peripheral nerve and usually affects skin or subcutaneous tissue. 3,4 Neurofibroma is generally presented in background of Von Recklinghausen's disease, but it can also appear solitarily. 5 This tumor is usually found in the head and neck and the flexor surfaces of the extremities.…”
Section: Introductionmentioning
confidence: 99%